Measures Towards Nearly Zero Energy Houses in Cyprus - Kalogirou, Soteris A. (My University, 2013)
According to the recast of the Energy Performance of Buildings Directive (EPBD), after 2020 all new buildings should have nearly zero energy consumption. For the public sector this Directive will be applied two years in advance. Although the term “nearly zero” is not quantified in the Directive, here it means a total primary annual energy consumption of less than 15 kWh/m2. There is thus a need to investigate ways to achieve this nearly zero energy consumption first by applying various thermal load reduction measures and then renewable energy systems. Therefore, in this paper, various measures are investigated as applied to a hypothetical typical house, 196 m2 in area located in Nicosia, Cyprus, to achieve this low energy consumption. These measures concern the use of insulation, type of glazing, natural ventilation, shape of the building and use of overhangs. The building is modeled with TRNSYS using the detailed Transfer Function Method (TFM). The baseline scenario, which involves a building with non-insulated walls and roof and single-glazed windows, shows a consumption of 297.7 kWh/m2 per year. From the measures investigated the most effective are the insulation and the use of advanced glazing systems, which reduce drastically the cooling load requirement but increase the heating load, although the total annual effect is the reduction of the total consumption. Natural ventilation has a smaller but significant effect. A solar water heater is also installed on the house to provide the hot water requirements of the occupants. The total contribution of this system is 6480 MJ or 9.2 kWh/m2 per year. The results show that a considerable reduction can be obtained from the above measures, which could lower the consumption to 88.27 kWh/m2 per year, but they are not enough to reach the target required unless an additional renewable energy system is installed to produce some of the energy consumed. Therefore, for the best case of measures examined, a 9.6 kWp polycrystalline PV system is required to be installed so as the building could achieve the required consumption of 15 kWh/m2.
Keywords: Energy Performance of Buildings Directive; Nearly Zero Energy Consumption; TRNSYS; Renewable Energy